2021
DOI: 10.1109/tnsre.2020.3038173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Targeted Assistance and Perturbations on the Relationship Between Pelvis Motion and Step Width in People With Chronic Stroke

Abstract: Background. People with chronic stroke (PwCS) often exhibit a weakened relationship between pelvis motion and paretic step width, a behavior important for gait stabilization.We have developed a force-field able to manipulate this relationship on a step-by-step basis.Objective. The objective of this study was to investigate the effects of a single exposure to our novel force-field on the step-by-step modulation of paretic step width among PwCS, quantified by the partial correlation between mediolateral pelvis d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Future experiments could gain causal insight by manipulating biomechanical gait metrics and determining whether clinical balance measures change in parallel. For example, we have demonstrated that targeted perturbations can influence step width modulation in both neurologically-intact controls [33] and PwCS [27], with a primary effect on ρFP [26]. It is presently unclear whether an intervention targeting increased paretic ρFP would produce parallel improvements in clinical balance measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future experiments could gain causal insight by manipulating biomechanical gait metrics and determining whether clinical balance measures change in parallel. For example, we have demonstrated that targeted perturbations can influence step width modulation in both neurologically-intact controls [33] and PwCS [27], with a primary effect on ρFP [26]. It is presently unclear whether an intervention targeting increased paretic ρFP would produce parallel improvements in clinical balance measures.…”
Section: Discussionmentioning
confidence: 99%
“…Following prior methods 32, 40, 41 , throughout each step we calculated the mediolateral displacement of the pelvis (relative to the stance heel at the start of the step) and the mediolateral velocity of the pelvis, with the positive direction defined as toward the swing leg. Pelvis displacement and velocity trajectories within each step were resampled to create 101-sample vectors, allowing us to perform analyses across these time-normalized steps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, individuals with lower limb amputation or post-stroke patients exhibit a gait with larger step width compared to non-disabled peers [17]- [20]. It has been postulated that this behavior is a result of poorer sensorimotor integration, where individuals after stroke fail to accurately integrate the position of their stance limb and pelvis to then place their swing foot appropriately [21]. Despite increased metabolic cost [22], [23], these populations prefer to walk with wider steps, implying the prioritization of stability and balance during the gait.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of foot placement control has been shown to increase as an after-effect following training sessions within a perturbing force-field, both in stroke patients [12], and in neurologically intact individuals [13, 14]. Even in neurologically intact individuals, CoM variations are not entirely accounted for by subsequent modulation in foot placement [5].…”
Section: Introductionmentioning
confidence: 99%